Laboratory Diagnosis of Lupus Anticoagulants: A Systematic Review of Assay Performance, Pre-analytical Challenges, and Clinical Utility - Wahyu Agus Prastyo; Artha Investari Nugraheni; Mutia Ruliana Ayuningrum (International Medical Journal Corp. Ltd, 2025)
Introduction: Lupus Anticoagulants (LA) are a heterogeneous group of autoantibodies that paradoxically increase the risk of thrombosis despite prolonging in vitro phospholipid-dependent coagulation assays. As a key laboratory criterion for the diagnosis of Antiphospholipid Syndrome (APS), accurate LA detection is critical for patient management. However, the diagnostic process is fraught with challenges, including assay variability, pre-analytical errors, and significant interference from anticoagulant therapies. This systematic review synthesizes the current evidence on laboratory testing for LA to provide a comprehensive overview of best practices and persistent challenges. Methods: A systematic search of biomedical databases was conducted to identify studies evaluating the diagnostic accuracy of LA assays, the impact of pre-analytical and analytical variables, strategies for mitigating anticoagulant interference, and the correlation of LA positivity with clinical outcomes. Studies were selected based on predefined inclusion and exclusion criteria. The methodological quality of diagnostic accuracy studies was assessed using the Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2) tool. Data on study design, patient populations, assays, and key outcomes were extracted and synthesized. Results: The review included 17 key studies. The evidence confirms that a dual-assay strategy using a dilute Russell's Viper Venom Time (dRVVT) and a sensitive activated Partial Thromboplastin Time (aPTT), such as the Silica Clotting Time (SCT), provides the highest diagnostic yield. The dRVVT demonstrates high specificity (>95%) and superior robustness to pre-analytical variations, whereas the SCT can offer greater sensitivity (up to 53.3% vs. 31.1% for dRVVT in one cohort). Pre-analytical variables, particularly platelet contamination, significantly risk false-negative results. Anticoagulant therapies, especially Direct Oral Anticoagulants (DOACs), cause profound interference, with rivaroxaban and apixaban leading to high rates of false-positive results (up to 92% for dRVVT). DOAC-adsorbent agents and alternative assays like the Taipan Snake Venom Time/Ecarin Time (TSVT/ET) have shown high efficacy in mitigating this interference. Persistent LA positivity is strongly associated with thrombosis (Odds Ratio up to 10.1 when co-present with other antiphospholipid antibodies) and adverse pregnancy outcomes (70% of pregnancies affected in one high-risk cohort). Discussion: The findings underscore the necessity of stringent, multi-step laboratory protocols for reliable LA detection. The differential performance and stability of dRVVT and SCT have important implications for assay selection, particularly in laboratory networks with sample transport. The management of anticoagulant interference has evolved from a strategy of avoidance to one of active mitigation, representing a significant advance in diagnostic capability and patient safety. The strong correlation between LA test results and severe clinical outcomes highlights the critical role of the laboratory in guiding therapeutic decisions, such as the choice between Vitamin K antagonists and DOACs in high-risk APS patients. Conclusion: Accurate LA detection is achievable but demands meticulous attention to pre-analytical, analytical, and post-analytical factors. Laboratories must implement robust protocols for sample processing and adopt validated strategies to manage anticoagulant interference. Clinicians must be aware of test limitations and the importance of confirming positive results. Continued efforts toward standardization, including the adoption of automated interpretation algorithms, are essential to reduce inter-laboratory variability and improve patient outcomes.